ANALYSIS OF HARMONIZATION OF SHARIA FINANCING TAX REGULATIONS BETWEEN DSN-MUI FATWA NO. 123/DSN-MUI/XI/2018 AND PP NO. 25 OF 2009 - Rismawati, Eva Nur; Isman, Isman; Budiman, Mamdukh (istinbath, 2025)
This research is a juridical analysis that examines the harmony of legal norms governing the tax treatment of Islamic financing in Indonesia, drawing on MUI DSN Fatwa No. 123/2018 and Government Regulation No. 25 of 2009. The results of the study show juridical disharmony, where the Fatwa prohibits the recognition of tax from customers as income by Islamic financial institutions (LKS). At the same time, government regulations treat it as a valid income tax asset. This discrepancy creates potential normative conflicts and legal uncertainty, and can weaken the principles of maqashid sharia in national economic practice. The findings underscore the pressing need for legal harmonization by applying the non-contradiction principle to reconcile positive law with Sharia principles. In practical terms, revising PP No. 25 of 2009 or issuing new technical regulations is necessary to accommodate the characteristics of Islamic law. Furthermore, the study recommends future research on integrating the Sharia taxation system within the national legal framework. It encourages comparative studies with other Muslim-majority countries to support the realization of a fair, sustainable, and law-abiding Sharia financing system.